Acetylsalicylic acid disrupts SARS-CoV-2 spike protein glycosylation and selectively impairs binding to ACE2 - Perico, Luca; Bovio, Alessandra; Tomasoni, Susanna; Trionfini, Piera; Cerullo, Domenico; Corna, Daniela; Pezzotta, Anna; Locatelli, Monica; Alberti, Marta; Benigni, Ariela; Remuzzi, Giuseppe (Frontiers in Immunology, 2026)
Preclinical and clinical evidence suggested the potential benefits of treatment with acetylsalicylic acid (ASA) in mitigating COVID-19 severity. While available studies largely focused on the intracellular pathways through which ASA impairs viral replication or dampens host immunoresponse stimulated by SARS-CoV-2, whether ASA directly affects the interaction between the viral spike protein and its cellular receptor angiotensin converting enzyme 2 (ACE2) remains unexplored. This question is clinically relevant, as circulating spike S1 has been shown to persist in patients with acute and long COVID-19, where its interaction with the broadly expressed ACE2 drives systemic manifestations and tissue damage. Here, we demonstrate that pre-incubation of the SARS-CoV-2 spike subunit 1 (S1) with ASA dose-dependently impaired ACE2 binding on Vero cells. The functional relevance of this finding was confirmed in transgenic mice with human ACE2, in which intratracheal administration of ASA-treated S1 markedly reduced lung injury, fibrosis, and inflammation compared to untreated S1. Glycoproteomic profiling revealed that ASA altered the glycosylation landscape of S1, particularly N-glycosylation at N61 and O-glycosylation at S325. Site-directed mutagenesis of these two residues confirmed the critical role of their glycosylation in S1-ACE2 binding in vitro. Consistently, the glycosylation-insensitive S1 had limited effect in inducing lung injury, fibrosis, and inflammation in transgenic mice compared to WT S1, phenocopying the protective effects of ASA. These findings unveil a previously unrecognized antiviral activity of ASA, providing a molecular rationale for its repurposing as a low-cost, readily available intervention to prevent the progression from mild to severe COVID-19.